2018
DOI: 10.1029/2018jc014320
|View full text |Cite
|
Sign up to set email alerts
|

Interconnectivity Between Volume Transports Through Arctic Straits

Abstract: Arctic heat and freshwater budgets are highly sensitive to volume transports through the Arctic‐Subarctic straits. Here we study the interconnectivity of volume transports through Arctic straits in three models; two coupled global climate models, one with a third‐degree horizontal ocean resolution (High Resolution Global Environmental Model version 1.1 [HiGEM1.1]) and one with a twelfth‐degree horizontal ocean resolution (Hadley Centre Global Environment Model 3 [HadGEM3]), and one ocean‐only model with an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
5
16
0
Order By: Relevance
“…Generally we find Arctic to North Atlantic oceanic volume and freshwater transports simulated with UKESM1 compare well with the available observational estimates and are accurate enough for the model to simulate the historical state of the Arctic‐North Atlantic exchanges. The mean volume transport through the Fram Strait in UKESM1 simulated over 1997–2014 of 2.4 ± 0.98 Sv is well within the observational range of 2.2 ± 2.1 Sv (de Boer et al., 2018). Observational estimates of the Fram Strait fresh water transport depend on the reference salinity, whether shelf or Atlantic water component are accounted for, on the layout of the moored instruments, and on the data interpolation strategy (as highlighted by the observed uncertainty in Figures 21d and 21e).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Generally we find Arctic to North Atlantic oceanic volume and freshwater transports simulated with UKESM1 compare well with the available observational estimates and are accurate enough for the model to simulate the historical state of the Arctic‐North Atlantic exchanges. The mean volume transport through the Fram Strait in UKESM1 simulated over 1997–2014 of 2.4 ± 0.98 Sv is well within the observational range of 2.2 ± 2.1 Sv (de Boer et al., 2018). Observational estimates of the Fram Strait fresh water transport depend on the reference salinity, whether shelf or Atlantic water component are accounted for, on the layout of the moored instruments, and on the data interpolation strategy (as highlighted by the observed uncertainty in Figures 21d and 21e).…”
Section: Resultssupporting
confidence: 77%
“…The key reasons for this are the large distance between the moorings, changes in instrumental layout from year‐to‐year, and absence of the observations on the Greenland continental shelf. The later requires the gap in the shelf transports to be filled with model estimates or extrapolate the data from nearest moorings (e.g., de Boer et al., 2018). The differences in the interpolation procedures can also introduce a large uncertainty in transport calculations.…”
Section: Model and Datamentioning
confidence: 99%
“…They show that in the Nordic seas, the climatology of the model is an improvement over its lower-resolution counterpart and is consistent with observations in terms of ocean volume transport (Hansen and Østerhus 2000;Fahrbach et al 2001;Jónsson and Briem 2003;Macrander et al 2005), precipitation (Xie and Arkin 1997), winter sea ice, sea level pressure (Uppala et al 2005), and sea surface temperature and salinity (Conkright et al 2002). Several other studies have also demonstrated that HiGEM has a good representation of the Arctic when compared with observations (Lique et al 2015;de Boer et al 2018).…”
Section: A Model and Experimentsmentioning
confidence: 85%
“…More recently, Muilwijk et al (2018) analyzed the variability in a century-long forced simulation of the same model. de Boer et al (2018) studied the variability of volume transports through the Arctic straits and their correlations using both a 1/38 and a 1/128 coupled model similar to GC3. The ongoing HighResMip experiments (Roberts et al 2019) will provide new opportunities to investigate the multidecadal variability of the AW inflow into the Arctic.…”
Section: Interannual Variability Of Heat Exchanges Between the Greenland-iceland And Norwegian Seasmentioning
confidence: 99%